Drugs and money managing the drug trade and crime money in Europe - Duyne, Petrus C. van 1946-; Levi, Michael 1948- (Routledge, 2005)
(Publisher-supplied data) Drugs and Money covers a diverse range of subjects, starting with an analysis of the policy of fear in which law enforcement is haunted by drug money. In this intriguing book, Petrus C. van Duyne and Michael Levi introduce the reader to an ever-unfolding series of problems: mind control, mind-influencing substances, the complications of international drug regulation, and the interaction between markets and actors, with the consequent amassing of huge amounts of crime-money. The social and economic aspects of crime-money are reconsidered and described in terms of the threat they pose to the legitimate economy.
Includes bibliographical references and index
Keywords: Drogue, Lutte contre la - Europe; Drogues - Trafic - Aspect économique - Europe; Drogues - Trafic - Europe; Drogues et criminalité - Europe; Georganiseerde misdaad; Witwassen; Drug traffic -- Europe; Drug traffic -- Economic aspects -- Europe; Drug control -- Europe; Drug abuse and crime -- Europe; Drogenhandel; Drogenkriminalität; Europa